Optimalisasi Aplikasi Macromedia Flash 8 Dalam Pembelajaran Kosakata Bahasa Arab - Muhammad Yusuf; Eka Dewi Rahmawati (LP2M IAIN Sultan Amai Gorontalo, 2020)
Language learning in the era of industrial revolution 4.0 is also influenced by technology information development, for example, on using an application in the teaching and learning process. The application is usually using as a medium for improving language skills or language components, such as vocabulary. One application is efficient and effective in teaching the Arabic language, especially Arabic language vocabulary is a Macromedia flash 8 application. The application can be used to solve the problem which still constraint the Arabic teacher and also the students. This article aims to research the Macromedia flash 8 application in learning Arabic vocabularies. This research used a research design method with procedures, need analysis, application design, application implementation, application evaluation, and application validation. The subject of this research was Islamic junior student's grade IX. The result showed that Macromedia flash 8 application was effective in improving students’ vocabulary, especially related to Islamic fasting, Ied Al-Adha, and hobby. They were presented using text, graphics, and animation.